Natriuresis During an Acute Intravenous Sodium Chloride Infusion in Conscious Sprague Dawley Rats Is Mediated by a Blood Pressure-Independent α1-Adrenoceptor-Mediated Mechanism - Frame, Alissa A.; Nist, Kayla M.; Kim, Kiyoung; Kuwabara, Jill T.; Wainford, Richard D. (Frontiers in Physiology, 2022)
The mechanisms that sense alterations in total body sodium content to facilitate sodium homeostasis in response to an acute sodium challenge that does not increase blood pressure have not been fully elucidated. We hypothesized that the renal sympathetic nerves are critical to mediate natriuresis via α1- or β-adrenoceptors signal transduction pathways to maintain sodium balance in the face of acute increases in total body sodium content that do not activate the pressure-natriuresis mechanism. To address this hypothesis, we used acute bilateral renal denervation (RDNX), an anteroventral third ventricle (AV3V) lesion and α1- or β-antagonism during an acute 1M NaCl sodium challenge in conscious male Sprague Dawley rats. An acute 1M NaCl infusion did not alter blood pressure and evoked profound natriuresis and sympathoinhibition. Acute bilateral RDNX attenuated the natriuretic and sympathoinhibitory responses evoked by a 1M NaCl infusion [peak natriuresis (μeq/min) sham 14.5 ± 1.3 vs. acute RDNX: 9.2 ± 1.4, p < 0.05; plasma NE (nmol/L) sham control: 44 ± 4 vs. sham 1M NaCl infusion 11 ± 2, p < 0.05; acute RDNX control: 42 ± 6 vs. acute RDNX 1M NaCl infusion 25 ± 3, p < 0.05]. In contrast, an AV3V lesion did not impact the cardiovascular, renal excretory or sympathoinhibitory responses to an acute 1M NaCl infusion. Acute i.v. α1-adrenoceptor antagonism with terazosin evoked a significant drop in baseline blood pressure and significantly attenuated the natriuretic response to a 1M NaCl load [peak natriuresis (μeq/min) saline 17.2 ± 1.4 vs. i.v. terazosin 7.8 ± 2.5, p < 0.05]. In contrast, acute β-adrenoceptor antagonism with i.v. propranolol infusion did not impact the cardiovascular or renal excretory responses to an acute 1M NaCl infusion. Critically, the natriuretic response to an acute 1M NaCl infusion was significantly blunted in rats receiving a s.c. infusion of the α1-adrenoceptor antagonist terazosin at a dose that did not lower baseline blood pressure [peak natriuresis (μeq/min) sc saline: 18 ± 1 vs. sc terazosin 7 ± 2, p < 0.05]. Additionally, a s.c. infusion of the α1-adrenoceptor antagonist terazosin further attenuated the natriuretic response to a 1M NaCl infusion in acutely RDNX animals. Collectively these data indicate a specific role of a blood pressure-independent renal sympathetic nerve-dependent α1-adrenoceptor-mediated pathway in the natriuretic and sympathoinhibitory responses evoked by acute increases in total body sodium.